Cell-Based Antioxidant Properties and Synergistic Effects of Natural Plant and Algal Extracts Pre and Post Intestinal Barrier Transport - Christophe Furger; Camille Gironde; Mylène Rigal; Cécile Dufour; Damien Guillemet (MDPI AG, 2022)
In this work, both direct and indirect cell-based antioxidant profiles were established for 27 plant extracts and 1 algal extract. To evaluate the direct antioxidant effects, fluorescent AOP1 cell assay was utilized, which measures the ability of different samples to neutralize intracellular free radicals produced by a cell-based photo-induction process. As the intestinal barrier is the first cell line crossed by the product, dose response curves obtained from Caco-2 cells were used to establish EC50 values for 26 out of the 28 natural extracts. Among them, 11 extracts from Vitis, Hamamelis, Syzygium, Helichrysum, Ilex and Ribes genera showed remarkable EC50s in the range of 10 µg/mL. In addition to this, a synergistic effect was found when combinations of the most potent extracts (S. aromaticum, H. italicum, H. virginiana, V. vinifera) were utilized compared to extracts alone. Indirect antioxidant activities (i.e., the ability of cells to trigger antioxidant defenses) were studied using the ARE/Nrf2 luminescence reporter-gene assay in HepG2 cells, as liver is the first organ crossed by an edible ingredient once it enters in the bloodstream. Twelve extracts were subjected to an intestinal epithelial barrier passage in order to partially mimic intestinal absorption and show whether basolateral compartments could maintain direct or indirect antioxidant properties. Using postepithelial barrier samples and HepG2 cells as a target model, we demonstrate that indirect antioxidant activities are maintained for three extracts, S. aromaticum, H. virginiana and H. italicum. Our experimental work also confirms the synergistic effects of combinations of post-intestinal barrier compartments issued from apical treatment with these three extracts. By combining cell-based assays together with an intestinal absorption process, this study demonstrates the power of cell systems to address the issue of antioxidant effects in humans.